Embedded Information Literacy Instruction for Upper Level Engineering Undergraduates in an Intensive Writing Course. Issue 4 (2nd October 2018) - Stephens, Jane; Melgoza, Pauline; Hubbard, David E.; Pearson, Chad J.; Wan, Gary
ABSTRACT: This study describes and assesses a pilot program to provide information literacy instruction to undergraduate engineering students in a writing intensive course. Working in teams, students complete a professional paper that requires them to identify and analyze a topic on mechanical power. Instruction is delivered through a consultation model that embeds librarians in student teams. Findings indicate that these students receive customized instruction, use the class guide to identify and access library resources independently, and to a lesser extent, use interlibrary loan to acquire needed materials. Scalability is challenging, but suggestions for improvement are discussed.